The Paleocene-Eocene transition in the subtropical Pacific Ocean (Shatsky Rise, Leg 198) : inference from planktonic foraminifera - Maria Rose Petrizzo (null, 2006)
The Paleocene-Eocene interval was cored during Leg 198 at four sites (1209 to 1212) in a depth range of 2387 m to 2907 m, and corresponds to an 8- to 23-cm-thick layer of clayey nannofossil ooze with a sharp base and a gradational upper contact. Detailed analysis on two selected holes (1209B and 1210B), were performed with high-resolution cm-scale sampling extended below and above the clay-rich layer for few centimetres. A total of 80 samples were analysed for planktonic foraminifera. At these sites the Paleocene yellowish brown calcareous ooze is overlain by a thin dark brown clay seam (~ 2 mm) which corresponds to the base of the Paleocene-Eocene Thermal Maximum (PETM) and to the Paleocene/Eocene boundary. At Shatsky Rise, the onset of the PETM is marked by the abrupt onset of the negative carbon isotope excursion (CIE) which lies just below the sharp lithologic contact between more carbonate-rich ooze overlying clay-rich ooze. In the upper part of the PETM interval, the clay-rich ooze gradually becomes more carbonate rich and carbon isotope values gradually increase. A high-resolution centimeter-scale quantitative analysis of the planktonic foraminiferal assemblages was performed in order to provide a high resolution bio-chemostratigraphic correlation across the Paleocene/Eocene boundary and to document the composition of the planktonic foraminiferal assemblages. Quantitative analyses well document the similarity in composition of the planktonic foraminiferal assemblages between the two sites. In general, Morozovella dominates the assemblages and its maximum relative abundance is coincident with the carbon isotope excursion. Subbotinids show an opposite trend and are absent in the interval of maximum abundance of Morozovella. A decrease in abundance of about 10% in average is observed within the Acarinina group from the base to the top of the studied sections. The excursion taxa first appear at the CIE and rich their maxima abundance (10%) at the beginning of the morozovellids decline. A minimum in species ...